A refractive index sensor based on metal-insulator-metal coupling ring resonator with a stub - Cao, Yuhao; Yan, Shubin; Liu, Feng; Wang, Jin; Chang, Shuwen; Liu, Guang; Zhang, Wei; Wu, Taiquan; Ren, Yifeng (Frontiers in Physics, 2024)
In this work, a refractive index sensor structure is proposed, which consists of the met-al-insulatormetal (MIM) waveguide coupling with ring resonator with a rectangular cavitystub-2. Its sensing characteristics are analyzed by the finite element analysis method. SPPs is an electromagnetic wave mode excited by the oscillatory coupling of free electron-photon interactions on the surface region of a metal, whose field strength is maximum at the metal-dielectric partition interface and then decays exponentially to both sides The results show that the sensing characteristics of the ring resonator can be changed by introducing a stub, which can achieve the purpose of enhancing the coupling efficiency of SPPs. The structure has two Fano peaks, and each peak can be individually regulated by changing the size of the sensing structure. Sensitivity is the key performance indicator of the system, which is the shift in resonance wavelength caused by a change in refractive index when the ambient medium is changed. The best sensitivity of this structure can reach 2300nm/RIU with a figure of merit (FOM)FOM value of 60 RIU -1 . The proposed structure has great potential in nano-sensors.